How palladium inhibits CO poisoning during electrocatalytic formic acid oxidation and carbon dioxide reduction - Chen, Xiaoting; Granda-Marulanda, Laura P.; McCrum, Ian T.; Koper, Marc T. M. (Nature communications, 2022)
Development of reversible and stable catalysts for the electrochemical reduction of CO 2 is of great interest. Here, we elucidate the atomistic details of how a palladium electrocatalyst inhibits CO poisoning during both formic acid oxidation to carbon dioxide and carbon dioxide reduction to formic acid. We compare results obtained with a platinum single-crystal electrode modified with and without a single monolayer of palladium. We combine (high-scan-rate) cyclic voltammetry with density functional theory to explain the absence of CO poisoning on the palladium-modified electrode. We show how the high formate coverage on the palladium-modified electrode protects the surface from poisoning during formic acid oxidation, and how the adsorption of CO precursor dictates the delayed poisoning during CO 2 reduction. The nature of the hydrogen adsorbed on the palladium-modified electrode is considerably different from platinum, supporting a model to explain the reversibility of this reaction. Our results help in designing catalysts for which CO poisoning needs to be avoided. Understanding how palladium inhibits CO poisoning is important for rational design of enhanced catalysts. Here the authors show high formate coverage on the palladium-modified electrode inhibits poisoning during formic acid oxidation and the adsorption of CO precursor dictates the delayed poisoning during CO2 reduction.